Ascent and descent cones of ordered median block functions. (4th May 2018) - Grzybowski, J.; Kalcsics, J.; Nickel, S.; Pallaschke, D.; Urbański, R.
Abstract: In this paper, we study properties of a special class of ordered median functions, called block-functions. These are ordered median functions which belong to a generating binary (row)-vector of the form called a block vector. The aim of this paper is to explicitly determine the simplicial complexes and all steepest descent and ascent directions of descent and ascent cones of ordered median block-function.